Indigenous Inland Fish Traps and Pots of Maharashtra, India - LEKSHMI, MANJU; KK, Prajith; Leela Edwin (Fishery Technology, 2023)
Variety of trap designs are operational in the inland and marine waters of India. Limited records are available on the structure and operational aspects of fish traps, especially from inland waters. A study was carried out for documentation of traditional fish trapping devices along six districts of Maharashtra. Of the traps surveyed, typical designs were identified such as rectangular, conical, and cylindrical either baited or un-baited, with or without funnels. Traps are eco-friendly fishing gears and their structure and designs vary with the region as well as the availability of materials. Over the period, the number of traditional fishing traps is decreasing due to various facts viz. non-availability of raw materials, lack of expertise for construction, low catch rate etc. Most of the depicted traps were indigenous, used for capturing crabs, shrimps, and small finfish from the inland waters, and actively operated during the pre and post-monsoon season as a livelihood option for the fishers. There is a possibility for modernising the traditional fish traps with the most efficient designs and durable gear materials for recuperating the efficiency, which will ultimately improve the life of fishers.